O adaptacji, ekranizacji, przekładzie intersemiotycznym i innych zmartwieniach teorii literatury, filmu i mediów - Choczaj, Małgorzata (Wydawnictwo Naukowe UAM, 2011)
The basis of this deliberation is a critical discussion of common perspectives and research methodology concerning the notion of adaptation. The author searches for universal adaptation models, describes creating new techniques of translation and examines relations among arts. The aim of reminding and critical discussion of the state of research of adaptation is to find the threats referring to common acceptance of one research paradigm, i.e. the perspective of literary studies and semiotics. One of the effects of such a way of thinking may be ungrounded equating a book with a literary work as such, as well as perceiving a film as something second-rate, which often functions only in reference to a book. The author, who refers to Werner Faulstich’s concept of the media, sees the paradigm which is currently binding in the research of adaptation as incomplete and inconsistent. Thus, she is inclined to accept the point of view of media experts. According to that viewpoint, both the book and the film seem to be the media that process and transfer literature (a particular story, e.g. War of the Worlds) in accordance with the principles of its own aesthetics. The concept encourages to change the scientific paradigm and liberates the notion of adaptation from all kinds of the consequences assumed by literary studies. It also allows to concentrate on the aesthetics of a particular medium.
Adaptation, film adaptation, intersemiotic translation and other concerns of the theory of literature, film and media